2020
DOI: 10.21608/jppp.2020.166218
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Abamectin and Buprofezin Residues in Eggplant and Pepper Plants

Abstract: Eggplant and pepper plants were sprayed with abamectin and buprofezin, respectively once at the recommended rate to study the residues and effect of tap water and acetic acid (1%) treatment as washing solution on their residues. Their risk assessment was also studied and summarized results show the following: The initial amounts of each pesticide in leaves of eggplant and pepper were much higher than the fruits. Loss percentages in residue amounts were higher in eggplant and pepper fruits than leaves. The wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Ajeep et al's s tudy on the effect of washing with tap water and washing with an acetic acid solution on the residual amount of five insecticides (dimethoate, carbaryl, chlorpyrifos, cypermethrin, and fenvalerate) and one herbicide (2, 4-dichloro phenoxy acetic acid) in tomato showed that both washing methods reduced the concentration of pes ticides by a maximum of 63.08% [30]. In Shalaby's s tudy, it was reported that washing with tap water and acetic acid (1%) could decrease the residual concentrations of abamectin and buprofezin in eggplant and pepper plants two hours after spraying up to 21.86% for washing with water and 41.68% with acetic acid [31]. In Hanafi et al's s tudy on okra, the initial residual concentration for chlorfenapyr and acetamiprid was reported to be 7.5 mg kg -1 and 0.8 mg kg -1 , respectively, which after washing the okra with water, the residual reduction percentage was reported to be 90% for chlorfenapyr and 48% for acetamiprid.…”
Section: Comparison Of Different Conditionmentioning
confidence: 99%
“…Ajeep et al's s tudy on the effect of washing with tap water and washing with an acetic acid solution on the residual amount of five insecticides (dimethoate, carbaryl, chlorpyrifos, cypermethrin, and fenvalerate) and one herbicide (2, 4-dichloro phenoxy acetic acid) in tomato showed that both washing methods reduced the concentration of pes ticides by a maximum of 63.08% [30]. In Shalaby's s tudy, it was reported that washing with tap water and acetic acid (1%) could decrease the residual concentrations of abamectin and buprofezin in eggplant and pepper plants two hours after spraying up to 21.86% for washing with water and 41.68% with acetic acid [31]. In Hanafi et al's s tudy on okra, the initial residual concentration for chlorfenapyr and acetamiprid was reported to be 7.5 mg kg -1 and 0.8 mg kg -1 , respectively, which after washing the okra with water, the residual reduction percentage was reported to be 90% for chlorfenapyr and 48% for acetamiprid.…”
Section: Comparison Of Different Conditionmentioning
confidence: 99%